PANDANGAN PARA ULAMA TERHADAP IDDAH PEREMPIIAN HAMIL DI LUAR NIKAH - Fathurrahman Azhari (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
lslamjc law impDsos a waiting penod belbre rernanl for a prcgnant wonran who is d;vorccd or because the lusban(l passcs aay. lhe waiting period for a prcgnani woman is ntil shc gives birth. For a wonan who is pregna.r s,ithoul gcling mnrried fit thc ulcrnar have rwo djtferenr viwsi a group who nill wan(s to inrpose the wailing a period. and a g.orp who docs not cons;der lhe wai(ins pcriod as an obligation. tach group has their o\!n argumenialion and law bic.